SREDNJOISTOČNO PORIJEKLO MODERNIH ZNANOSTI - Siddiqui, Dilnawaz A.; Smajić, Aid (Novi Muallim, 2011)
Izvorni naslov rada je “Middle Eastern Origins of Modern Sciences” i preuzet je iz knjige Muslim Contributions to World Civilization, M. Basheer Ahmed, Syed A. Ahsani i Dilnawaz A. Siddiqui (ured.), The International Institute of Islamic Thought, Herndon (2005.), str. 53-70. Prijevod s engleskog: Aid Smajić